The impact of computer modeling on the development of commitment to action in the application of decision conferencing to strategic issues: preliminary results from a field study - Wood, Margot; Pervan, Graham; Schmidenberg, Olive (University of New South Wales, 1998)
Decision-making is fundamental to organizational functioning. As much of the decision making, which occurs within organizations, involved groups of people working together, there has been a growth in research based on Group Decision Support systems (GDSS). Decision Conferencing is a form of GDSS, which utilizes computer modeling to support group decision making. Decision Conferencing rests on the premise that this process provides two crucial benefits to groups tying to solve problems: a) participants develop a shared understanding of the issue they are facing and b) the Decision Conferencing process fosters the generation of a commitment to act on the decision made. Whilst this assumption forms the basic justification for Decision Conferencing, there is no direct empirical evidence in the literature to support this claim. There fore, the focus of the proposed research is to explore participants, perceptions of this relationship, with special regard to the application of Decision Conferencing to strategic issues.